Post a New Question

pre calcalus

posted by .

(x+4)^2/3=9

  • pre calcalus -

    (x+4)^(2/3) = 9
    To do this, we raise both side by 3/2, so that the exponent 2/3 of the term on the left side will be cancelled:
    (x + 4)^(2/3 * 3/2) = 9^(3/2)
    (x + 4)^(1) = 3^3
    x + 4 = 27
    x = 27 - 4
    x = 23
    To check, substitute the x value to the original equation:
    (23 + 4)^(2/3) = 9
    27^(2/3) = 9
    3^2 = 9
    9 = 9
    Thus x is indeed equal to 23.

    Hope this helps~ :3

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question